Sustainable National Tourism Development Based on The Conservation of Nature and Culture of Traditional Law Communities - I Nyoman Nurjaya; I Nyoman Budiartha (Fakultas Hukum, Universitas Warmadewa, 2023)
Indonesia has a wealth of invaluable natural resources and potential cultural resources for developing national tourism, such as strategic geographical location, living and non-living natural resources, ethnic and linguistic diversity, historical and ancient heritage, and arts and traditions of inviting people. The aim research is to know the sustainable national tourism development based on the conservation of nature and culture of traditional law communities.the method used empirical research, a statutory approach, a conceptual approach, a case study approach, and a sociological approach. The result shows that Sustainable tourism development by the UNWTO is defined as a conscious effort and carried out in a planned manner by integrating economic, environmental, and socio-cultural elements of society into tourism development that is oriented towards improving the welfare of the local community. This means that the performance of sustainable tourism development is not solely intended to pursue economic growth to increase state income and foreign exchange (state revenue), but must be carried out in harmony with the interests of environmental conservation and preserving